HUBUNGAN DUKUNGAN KELUARGA DENGAN MOTIVASI PASIEN HIPERTENSI DALAM MELAKUKAN KUNJUNGAN ULANG DI POLIKLINIK PENYAKIT DALAM RSU ASTRINI WONOGIRI - Hana Rosiana Ulfah; Runi Daryati; Ahmad Syamsul Bahri (STIKES Estu Utomo, 2024)
Background : In patients with hypertension, family support plays a very important role in maintaining and controlling so that blood pressure does not increase and is expected to return to normal. In addition, blood pressure measurements can also be carried out by families who have learned from health workers. Hypertensive patients who do not receive family support can make it difficult for patients to always maintain good hypertension care. Objective : To find out the relationship of family support to the motivation of hypertensive patients to make repeat visits at the Internal Medicine Polyclinic, Astrini Hospital, Wonogiri. Methods : This research uses quantitative research with the research design used in this research is correlation analytic research. Results : The majority family support was sufficient, with a score range of 50 -75 as many as 26 people or 57%, the motivation of control patients to the majority hospital was sufficient, namely 59%, and the relationship significance value (p-value) was 0.042 at the alpha error level ( n)=5%. Conclusion : There is a relationship between family support and patient motivation to revisit the hospital.